TOPICAL QUESTIONS OF THE PROSECUTION IN LATVIAN CRIMINAL PROCEDURE IN COURT - Sumbarova, Marina (Administrative and Criminal Justice, 2019)
One of the institutions of criminal procedural law, which was subjected to change along with others, is the institution of prosecution in criminal procedure of Latvia. The judge, legally and reasonably makes a decision on charges of the criminal procedure for the assignment achievement of the criminal procedure, the person directing process. For this purpose, it is important to evaluate proofs objectively in a criminal case and make the correct decision to prosecute a person. The study of issues, related to the prosecution in judicial criminal procedure is determined in the paper from the point of view of Latvia’s and other scientists. Consideration of theoretical and practical provisions on the research topic allowed implementing individual conclusions and suggestions related to the accusation in judicial criminal procedure of Latvia that definitely will contribute to further improvement of the Criminal Procedural Law of Latvia